A 9-Month Jumping Intervention to Improve Bone Geometry in Adolescent Male Athletes. Issue 12 (December 2018) - VLACHOPOULOS, DIMITRIS; BARKER, ALAN R.; UBAGO-GUISADO, ESTHER; WILLIAMS, CRAIG A.; GRACIA-MARCO, LUIS
ABSTRACT: Purpose: Sports have different effects on bone development and effective interventions to improve bone health of adolescent athletes are needed. The purpose of the study was to investigate the effect of a 9-month jumping intervention on bone geometry and metabolism in adolescent male athletes. Methods: Ninety-three adolescent (14.1 yr old) male swimmers (SWI), footballers (FOO), and cyclists (CYC) were randomized to intervention and sport (INT-SWI = 19, INT-FOO = 15, and INT-CYC = 14) or sport only (CON-SWI = 18, CON-FOO = 15, and CON-CYC = 12) groups. Cross-sectional area, cross-sectional moment of inertia (CSMI), and section modulus (Z) at the femoral neck were assessed using hip structural analysis and trabecular texture of the lumbar spine using trabecular bone score. Bone mineral content (BMC) at femoral neck and lumbar spine was assessed using dual-energy x-ray absorptiometry. Serum N-terminal propeptide of procollagen type I, isomer of the carboxy-terminal telopeptide of type 1 collagen, total serum calcium, and 25-hydroxyvitamin D were analyzed. Results: INT-CYC acquired significantly higher lumbar spine BMC (4.6%) and femoral neck BMC (9.8%) than CON-CYC. INT-CYC acquired significantly higher cross-sectional area (11.0%), CSMI (10.1%), and trabecular bone score (4.4%) than CON-CYC. INT-SWI acquired significantly higher femoral neck BMC (6.0%) and CSMI (10.9%) than CON-SWI. There were no significant differences between INT-FOO and CON-FOO in any bone outcomes. N-terminal propeptide of procollagen type I significantly decreased in CON-SWI, INT-FOO, CON-FOO, and CON-CYC. Carboxy-terminal telopeptide of type 1 collagen significantly decreased in CON-SWI and CON-CYC. The 25-hydroxyvitamin D significantly increased in INT-CYC, CON-CYC, INT-FOO, and CON-FOO. Conclusions: A 9-month jumping intervention improved bone outcomes in adolescent swimmers and cyclists, but not in footballers. This intervention might be used by sports clubs to improve bone health of adolescent athletes. Abstract : Supplemental digital content is available in the text.